Aspirin Use on Incidence and Mortality of Gastrointestinal Cancers: Current State of Epidemiological Evidence - Huang, Wen-Kuan; Tu, Hui-Tzu; See, Lai-Chu (Current Pharmaceutical Design, 2015)
Aspirin has been one of the most widely used medications since its first synthesis more than 100 years ago. In addition to short-term use for pain and fever relief, regular use of aspirin has been shown to reduce the risk of cardiovascular diseases and strokes. The issue of regular aspirin use in cancer prevention is definitely promising, which has been supported by growing evidence from a number of observational studies and post-trial follow-up data. Among all cancers, aspirin is showing to be the most effective in reducing the risk of colorectal cancer, and even at lower doses demonstrates a 30-40% effectiveness in preventing colorectal cancer. Esophagus and stomach cancers are two cancers getting increased attention from emerging evidence of meta-analyses. Given the common side effects of aspirin, such as gastrointestinal complications, whether it is ready to take aspirin regularly for general population remains controversial since more studies are needed to clarify the net balance between harm and benefit. The decision might become more complicated since recently one molecular epidemiology study showed that different genetic traits may impact the effect of aspirin on colorectal cancer. Here we summarize recent evidence from meta-analyses related to gastrointestinal cancers. We reviewed updated observational studies and post-trial follow up data from randomized controlled trials focusing on the role of aspirin in the incidence and mortality of gastrointestinal cancers.
Keywords: Aspirin